SIGOES - Sistema de Gerenciamento de Ocorrências Escolares - Faba, Wisley de Lima (BRASIL, 2022)
Management systems are increasingly present in our daily lives, as society makes constant use of this modernization. And for this area to optimize processes, it has been receiving great attention from institutions, whether public or private. Information technology is deeply linked to our society, and the way we use it generates many benefits, making our lives more comfortable. Therefore, due to the advancement of this technology, educational institutions felt obliged to adopt means that would help in the management of this information, starting to use software that provided greater management of the procedures performed. The amount of existing systems or software to manage this information is undeniable, but most do not suit the management needs of schools, where there is a shortage of systems for recording school occurrences, which until then are recorded in occurrence books. In this context, the objective of this work was to develop a Web System for the Management of School Occurrences, with the purpose of speeding up the registration and searches of this information, allowing the school management team to quickly plan solutions for the events. The methodology used to develop this work was divided into 6 stages, Bibliographic Survey, Initial Proposal, Development, Implementation, Final Adjustments and Usability Assessment, which resulted in a good acceptance by the evaluators and fulfilled the proposed objective.